The impact of industrial robots on EU employment and wages: A local labour market approach - Chiacchio, Francesco; Petropoulos, Georgios; Pichler, David (Brussels, 2018)
"The authors of this working paper study the impact of industrial robots on employment and wages in six European Union countries, which make up 85.5 percent of the EU industrial robots market.